Design and Study UV Sterilization System For Covid19 - Raghad Wessam Al-Deen Kareem Abd (International Journal of Industrial Innovation and Mechanical Engineering, 2024)
This Project Focuses On The Disinfection Of Surfaces And Items From Microorganisms, Particularly COVID-19, Using Ultraviolet Radiation. UV Germicidal Irradiation, Particularly In The 200-280 Nm Range, Is Highly Effective In Killing Many Microorganisms. To Test Klebsiella, Two Designs Were Constructed Using Canadian UV Leds And Chinese UV LEDS. The Results Showed Successful Disinfection With A High Microorganism Killed Ratio. The Chinese Design Had The Highest Disinfection Percentage Ratio Of 69.24%, While The Canadian Design Achieved 89.66%. Although The Canadian Design Is More Expensive, It Shows Excellent Results And Is Worth The Cost.